THE EFFECT OF PARENTAL SUPPORT AND THE SCHOOL ENVIRONMENT ON STUDENT LEARNING OUTCOMES IN SOCIAL STUDIES FOR GRADE VIII AT THE UPTD OF SMP NEGERI 2 PEMATANGSIANTAR - Ester Novela Siregar; Anton Luvi Siahaan; Debbi Petra Meyana (RADJA PUBLIKA, 2025)
This study aims to determine the effect of parental support and the school environment on student learning outcomes in Social Studies for Grade VIII at the UPTD of SMP Negeri 2 Pematangsiantar. This study was quantitative and employed a survey method. The population was 349 students, with a sample size of 66 students drawn using purposive sampling. Data were collected through questionnaires that had been tested for validity and reliability and analyzed using multiple linear regression with the help of SPSS. The results showed that (1) parental support had a positive and significant effect on student learning outcomes, (2) the school environment had a positive and significant effect on student learning outcomes, and (3) parental support and the school environment simultaneously had a positive and significant effect on student learning outcomes in Social Studies. The coefficient of determination indicates that both independent variables contribute significantly to improving student learning outcomes. Based on these results, it can be concluded that the better the support from parents and the school environment, the higher the student learning outcomes. Therefore, collaboration between schools and parents needs to be continuously improved to create a conducive learning environment both at home and at school